Production of medium-chain length polyhydroxyalkanoates (PHA) from sugar-rich extracts and hydrolysates from white wine grape pomace - Silva, Juliana Inês Barros (2021)
The aim of this thesis was the production of polyhydroxyalkanoates (PHA), using grape pomace as substrate. Five bacterial strains, Pseudomonas citronellolis NRRL B-2504, Pseudomonas chlororaphis DMS 19603, Pseudomonas resinovorans NRRL B-2649, Pseudomonas stutzeri NRRL B-775 and Burkholderia sacchari DSM 17165, were studied. In a first part, shake flask tests were carried out using as substrate grape pomace subjected to three types of treatment: aqueous extract (1); and hydrolysates obtained by acid treatment (2) or by compressed hot water (HCW) (3). The aqueous extract was used for the cultivation of Ps. chlororaphis, Ps. citronellolis, Ps. resinovorans and Ps. stutzeri, while acid and HCW hydrolysates were tested for Ps. chlororaphis, Ps. citronellolis, Ps. resinovorans and B. sacchari. These assays demonstrated that the aqueous extract provided, not only a good cell growth, but also a good accumulation of PHA by most strains tested. Cultures with the hydrolysates under the tested conditions resulted in reduced cell growth and/or absence of polymer accumulation. In a second phase, bioreactor assays were performed with Ps. chlororaphis, Ps. citronellolis and Ps. resinovorans that were identified as having higher PHA production potential. The strains reached 16.7%, 14.3% and 17.4% polymer content in the biomass, respectively, with volumetric productivity values of 0.04-0.08 g/(L.h). All polymers were medium-chain length PHA (mcl-PHA), composed mainly of 3-hydroxydecanoate, 3-hydroxydodecanoate and/or 3-hydroxyoctanoate, and had molecular weight values between 1×105 Da and 3.1× 105 Da. Despite the similar temperature degradation, the polymers had different degrees of crystallinity: the mcl-PHA produced by Ps. chlororaphis the highest value (38.8%) and that of Ps. resinovorans had the lowest (10.2%). Thus, the grape pomace extract proved to be a suitable substrate for the production of biopolymers with different physicochemical properties and versatile characteristics that can be used in different applications.